Extremely low frequency magnetic fields regulate differentiation of regulatory T cells: Potential role for ROS‐mediated inhibition on AKT. Issue 2 (25th January 2016) - Tang, Ruijing; Xu, Yujun; Ma, Feiya; Ren, Jing; Shen, Sunan; Du, Youwei; Hou, Yayi; Wang, Tingting
Abstract : Our previous studies showed that extremely low frequency magnetic fields (ELF‐MFs) inhibited tumor growth and change proportion of splenic regulatory T cells (Treg cells). Here, we focus on the effect of ELF‐MFs on lung metastatic melanoma mouse model and the regulatory mechanism of ELF‐MFs on the differentiation of Treg cells. Tumor‐bearing mice were exposed to sham ELF‐MFs and ELF‐MFs (0.4 T, 7.5 Hz) 2 h/day for 27 days. Metastatic tumor burden of lung was significantly decreased after ELF‐MF treatment. Compared to the control group, expressions of matrix metalloproteinase (MMP2, MMP9) and forkhead box P3 (Foxp3) in lung nodules significantly decreased in the ELF‐MF group. Moreover, in vitro, after stimulated with anti‐CD3, anti‐CD28 antibodies and transforming growth factor‐β (TGF‐β) and treated with ELF‐MFs for 2 h, expression of Foxp3 in total T cells was significantly decreased. Differentiation rate of Treg cells was inhibited from 32.0% to 22.1% by ELF‐MFs. Furthermore, reactive oxygen species (ROS) was increased and phospho‐serine/threonine protein kinase (p‐AKT) was inhibited in both T cells and Jurkat cells. ROS scavenger N‐acetyl‐l ‐cysteine reversed inhibition of AKT pathway and expression of Foxp3 from 18.6% to 26.6% in T cells. Taken together, our data show that ELF‐MF exposure promoted the inhibitory effect of ROS on AKT pathway and decreased Foxp3 expression, which provides an explanation for why ELF‐MF exposure can inhibit differentiation of Treg cells and enhance antitumor effect in metastatic melanoma mouse model. Bioelectromagnetics. 37:89–98, 2016. © 2016 Wiley Periodicals, Inc.